Edukasi Kesehatan Reproduksi Remaja Di Karangtaruna Pendowohardjo - Pri Hastuti; Desi Ekawati (Lembaga Penelitian Dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2021)
Adolescence is the initial period of maturity of the reproductive organs in humans or the so-calledpuberty. Based on previous preliminary studies, adolescents prefer sources of reproductive health informationobtained from peers and parents, but if this is not given an explanation from health workers directly it will causedifferent perceptions from each teenager which can cause gaps. Based on the preliminary study, researchers areinterested in doing community service with the title